The Role of Millennial Generation in Traditional Culture Preservation through Social Media - Saefurrohman, Nandi (Kamara Journal, 2024)
The development of information technology, especially through social media, has had a great impact on various aspects of life, including the preservation of traditional culture. The millennial generation, who grew up in a digital environment, has great potential in maintaining and introducing local culture through social media platforms such as Instagram, YouTube, and TikTok. This research aims to explore the role of the millennial generation in preserving traditional culture through social media and its impact on cultural diversity. The results of the study show that social media has become an effective means of introducing and introducing various elements of traditional culture to a wider audience. However, the challenge faced is the potential for commodification and distortion of cultural values due to the presentation that prioritizes entertainment over education. On the other hand, the use of social media also opens up opportunities for collaboration between cultural communities and the dissemination of knowledge about traditional culture more widely. For this reason, more in-depth cultural education is needed so that cultural preservation is not only in the form of entertainment, but also reflects authentic cultural values. The study concludes that social media can be an effective tool in the preservation of traditional culture, provided that there is an effort to maintain a balance between entertainment and a deep cultural understanding.